A Conceptual Framework of The Islamic Human Development Index (I-HDI) and its Relationship with Maqāṣid Al-Sharī'ah - Hasbi, M. Zidny Nafi'; Munajat, Makhrus; Qoyum, Abdul (Univeristas Islam Bandung, 2023)
Measurement of development in general uses the Human Development Index (HDI) indicator, but this concept cannot yet be a comprehensive measure of human development. The concept of HDI has an aspect of inequality and only measures the material session, while the spiritual is not measured. Therefore, the Islamic Human Development Index (I-HDI) is here to provide solutions for measuring human development in a complex way by measuring people's welfare through material, spiritual, and moral aspects. The purpose of this study is to explain the concepts and indicators of the human development index from an Islamic perspective and their relevance to maqāṣid al-sharī'ah. This research uses a method with a descriptive qualitative approach, which is an effort to understand the concepts found in the research process, using content analysis techniques and library research or literature review. The findings from this study indicate that the concept of the Islamic Human Development Index (I-HDI) provides an overview of the achievement of human development based on maqāṣid al-sharīʿah by measuring material and non-material aspects. I-HDI is an attempt to translate conventional development concepts into an Islamic perspective, in which the analytical tool used is based on the five maqāṣid al-sharīʿah dimensions as indicators of human needs both materially and spiritually. The I-HDI measurement is based on five maqāṣid al-sharīʿah, namely the protection and safeguarding of religion (ad-dien), protection of the soul (an-nafs), protection of the mind (al-aql), protection of offspring (an-nasl), protection of property (al-maal).